Optimization models to improve efficiency in feeding pigs within the company “El Cerrillo” - Salazar Salazar, Elmer Bagner (2015)
The main object of the research is to develop linear optimization models to improve the feeding of pigs in the “El Cerrillo” SR. Ltda Company. Reque – Chiclayo - Peru, from March to August 2009. For this, it was made and proved the truth of scientific hypothesis: “The application of linear optimization models to improve the feeding of pigs considering: the weight maximization of pigs, lean meat percentage and the weight maximization formulated with feeds at minimum cost. The feeds minimization and the feed cost”. By performing a Non experimental Technological Research, descriptive correlational and transversal type, where the company was used as the population and the sample “El Cerrillo” SR. Ltda. The interview, the survey, and the company record were used as data collection instruments. To reach the general object and demonstrate the truth of hypothesis, deterministic mathematics multi object models linear type were determined, with this instruments the efficiency of mathematical optimization models was tested by stage (Starting from 10 to 20Kg, growth of 21 to 60 Kg, ending of 61 to 90 Kg, pregnant women and nursing mothers), by hypothesis testing of mean difference at the 95 % confidence level applied in to two groups (reference and sample) of 20 pigs. It was demonstrated the linear optimization models improve significantly to improve the feeding of pigs (weight maximizing of pigs, lean meat percentage and the weight maximization formulated with feeds at minimum cost. The feeds minimizing and the feed cost) in the company “El Cerrillo” SR. Ltda.